Opposing Effects of Chronic Stress and Weight Restriction on Cardiovascular, Neuroendocrine and Metabolic Function - Flak, Jonathan N. (2011)
Chronic stress is associated with dysregulation of energy homeostasis, but the link between the two is largely unknown. For most rodents, periods of chronic stress reduce weight gain. We hypothesized that these reductions in weight are an additional homeostatic challenge, contributing to the chronic stress syndrome. Experiment #1 examined cardiovascular responsivity following exposure to prolonged intermittent stress. We used radio-telemetry to monitor mean arterial pressure and heart rate in freely moving, conscious rats. Three groups of animals were tested: chronic variable stress (CVS), weight-matched (WM), and controls. Using this design, we can distinguish between effects due to stress and effects due to the changing body weight. WM, but not CVS, markedly reduced basal heart rate. Although an acute stress challenge elicited similar peak heart rate, WM expedited the recovery to baseline heart rate. The data suggest that CVS prevents the weight-induced attenuation of cardiovascular stress reactivity. Experiment #2 investigated hypothalamic-pituitary-adrenal axis and metabolic hormone reactivity to novel psychogenic stress. WM increased corticosterone area under the curve. CVS blunted plasma glucose, leptin, and insulin levels in response to restraint. Experiment #3 tested the effects of WM and CVS on PVN oxytocin and corticotrophin-releasing hormone mRNA expression. CVS increased, while WM reduced PVN CRH mRNA expression, whereas both CVS and WM reduced dorsal parvocellular PVN oxytocin mRNA. Overall, the data suggest that weight loss is unlikely to account for the deleterious effects of chronic stress on the organism, but in fact produces beneficial effects that are effectively absent or indeed, reversed in the face of chronic stress exposure.